Finding a solution: Heparinised saline versus normal saline in the maintenance of invasive arterial lines in intensive care. (November 2016) - Everson, Matthew; Webber, Lucy; Penfold, Chris; Shah, Sanjoy; Freshwater-Turner, Dan
Background: We assessed the impact of heparinised saline versus 0.9% normal saline on arterial line patency. Maintaining the patency of arterial lines is essential for obtaining accurate physiological measurements, enabling blood sampling and minimising line replacement. Use of heparinised saline is associated with risks such as thrombocytopenia, haemorrhage and mis-selection. Historical studies draw variable conclusions but suggest that normal saline is at least as effective at maintaining line patency, although recent evidence has questioned this. Methods: We conducted a prospective analysis of the use of heparinised saline versus normal saline on unselected patients in the intensive care of our hospital. Data concerning duration of 471 lines insertion and reason for removal was collected. Results: We found a higher risk of blockage for lines flushed with normal saline compared with heparinised saline (RR = 2.15, 95% CI 1.392–3.32, p ≤ 0.001). Of the 56 lines which blocked initially (19 heparinised saline and 37 normal saline lines), 16 were replaced with new lines; 5 heparinised saline lines and 11 normal saline lines were reinserted; 5 of these lines subsequently blocked again, 3 of which were flushed with normal saline. Conclusions: Our study demonstrates a clinically important reduction in arterial line longevity due to blockages when flushed with normal saline compared to heparinised saline. We have determined that these excess blockages have a significant clinical impact with further lines being inserted after blockage, resulting in increased risks to patients, wasted time and cost of resources. Our findings suggest that the current UK guidance favouring normal saline flushes should be reviewed.